Tempeh Croquettes (Stecu), a Delicious and Nutritious Snack, as a Traditional Healthy Food to Prevent Stunting - Naibaho, Mawan Frisanti; Putri Azzahroh; Aquarini Fajarianty Putri (Rajaki of Tulip Medika Publisher, 2025)
Background: toddlers are prone to nutritional problems. For toddlers, the fulfillment of nutritional needs that are provided properly can help in the process of growth and development. Stunting is a condition of chronic malnutrition and recurrent infections in children, such as height below the average standard. Child stunting is a serious problem, as it is associated with a greater risk of morbidity and mortality, obesity non-communicable diseases, poor cognitive development, and low productivity and income. One way to prevent and treat stunting is through supplementary feeding (PMT). PMT with the utilization of local resources, cheap, but full of nutrients such as tempeh is recommended. Purpose : This community service was carried out with the aim of overcoming the priority problem found in the TPMB Aquirini area Method: The method used in this community service involve lectures, discussions, and demonstrations. The study targeted mothers who have toddlers and cadres who are active in posyandu Result: The results of this community service, toddler mothers understand and so do the staff of posyandu related counseling and complementary therapy “STECU” which can be applied to overcome stunting Conclusion: Based on the evaluation conducted after the provision of counseling and the provision of additional food tempeh croquettes “STECU” during community service, the intervention provided went well and effectively with the results of mothers who had toddlers and also cadres were able to answer questions and could find out how to prevent and manage stunting in children Keywords: stunting, tempeh, nutrition education, parent role